МЕТОДЫ БЮДЖЕТНОГО РЕГУЛИРОВАНИЯ В СОЦИАЛЬНОЙ СФЕРЕ КАЗАХСТАНА (Journal of Economic Research & Business Administration, 2015)
The efficiency of methods of calculation of financial norms to a considerable degree depends on fullness and reliability of information on planned (actual) expenses, data for the network, staff and contingents of budget agencies,population size and composition, as well as on other indices.